The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.7196/sajog.2017.v23i1.1116
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional descriptive study of breastfeeding behaviour and galactogogue use among private-sector patients in Cape Town, South Africa

Abstract: Background. Failure to exclusively breastfeed is often caused by a perception of insufficient breastmilk supply. Galactogogues are frequently prescribed in these circumstances, but this is supported by sparse scientific data with safety concerns for both mother and infant. The exact extent of galactogogue use in South Africa (SA) is not well known. Objectives. To assess breastfeeding behaviour, galactogogue use and perceived galactogogue side-effects among patients attending International Board Certified Lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
3
6
4
Order By: Relevance
“…The current study showed that most lactating women obtained information on selected foods and special herbs from the home mostly parents and grandparents. Contrary to the ndings of the current study, some studies have reported the internet as a major source [11] , for other studies, friends and family [21] and health service providers [22,23] were the main sources of information on breastmilk production aids. Our results are consistent with the study by Budzynska et al [24] in which most cultures transfer knowledge of breastmilk productions aids from generation to generation.…”
Section: Discussioncontrasting
confidence: 97%
“…The current study showed that most lactating women obtained information on selected foods and special herbs from the home mostly parents and grandparents. Contrary to the ndings of the current study, some studies have reported the internet as a major source [11] , for other studies, friends and family [21] and health service providers [22,23] were the main sources of information on breastmilk production aids. Our results are consistent with the study by Budzynska et al [24] in which most cultures transfer knowledge of breastmilk productions aids from generation to generation.…”
Section: Discussioncontrasting
confidence: 97%
“…The current study showed that most lactating women obtained information on selected foods and special herbs from the home mostly parents and grandparents. Contrary to the ndings of the current study, some studies have reported the internet as a major source [11] , for other studies, friends and family [21] and health service providers [22,23] were the main sources of information on breastmilk production aids. Our results are consistent with the study by Budzynska et al [24] in which most cultures transfer knowledge of breastmilk productions aids from generation to generation.…”
Section: Discussioncontrasting
confidence: 97%
“…The high prevalence of lactogogue use among lactating women in both regions is consistent with earlier studies [25][26][27] but a little higher than reported in studies from some developed countries [11,23,28]. Wealth inequality could play a role in healthcare access and delivery, respondents in the current study (a developing country setting) where healthcare access is relatively low may be less likely to seek professional advice from healthcare professionals -resorting to information from the family on which foods and special herbs could be used to support breastmilk production.…”
Section: Discussionsupporting
confidence: 91%
“…The current study showed that most lactating women obtained information on selected foods and special herbs from the home mostly parents and grandparents. Contrary to the ndings of the current study, some studies have reported the internet as a major source [11], for other studies, friends and family [22] and health service providers [23,24] were the main sources of information on breastmilk production aids. Our results are consistent with the study by Budzynska et al [25] in which most cultures transfer knowledge of breastmilk productions aids from generation to generation.…”
Section: Discussioncontrasting
confidence: 93%